2000
DOI: 10.1049/ip-map:20000428
|View full text |Cite
|
Sign up to set email alerts
|

Scanned microstrip arrays using simple integrated ferrite phase shifters

Abstract: A phase-steered microstrip antenna array is presented, suitable for application as a mobile vehicle satellite terminal. Phase shifters are implemented on a hybrid dielectric-ferrite substrate, and use is made of the phase transition near the cut-off region of the biased ferrite. Small permanent magnets and carefully biased ferrites remove the need for large applied electromagnetic fields. 2-, 3-and 4-clement demonstrator arrays have been constructed, and np to 30 beam squint has been achieved For applied magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Biased ferrite devices are often avoided for battery supplied mobile systems as large drive currents are necessary to achieve significant phase shifts. However, it has been demonstrated that the requirement for a strong controllable magnetic field is removed by biasing the ferrite close to a region of resonance, [4]. This letter presents a method of utilizing ferrite substrates that require only a relatively small field change to steer the beam.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biased ferrite devices are often avoided for battery supplied mobile systems as large drive currents are necessary to achieve significant phase shifts. However, it has been demonstrated that the requirement for a strong controllable magnetic field is removed by biasing the ferrite close to a region of resonance, [4]. This letter presents a method of utilizing ferrite substrates that require only a relatively small field change to steer the beam.…”
Section: Introductionmentioning
confidence: 99%
“…In this work a static magnetic field was applied to bias the ferrite at the threshold of the magnetic absorption region where the effective permeability presented by the ferrite becomes negative and propagating modes are cut off, [4]. The steep phase progression associated with this phenomenon ensures that only small bias variations are needed to produce significant changes in the ferrite tensor permeability.…”
Section: Introductionmentioning
confidence: 99%
“…The integration of ferrite substrates with microstrip technology offers potential for achieving electromagnetic switching of component properties by the application of an external low frequency biasing magnetic field, [1][2][3]. It is possible to produce low complexity phase shifting structures for vehicle cruise control radar and interference rejection in future mobile systems.…”
Section: Introductionmentioning
confidence: 99%
“…However, a recurrent problem associated with ferrite components is the large current magnitudes necessary to achieve the conditions where the material permeability is described by a tensor. This letter presents a development of work [2,3] where the principle of using small bias variations near the magnetic resonant regions was demonstrated. Two complimentary phase shifters have been implemented and the small bias field shifts are provided by an electromagnet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation